Interdisciplinarity and (dis)integration in postgraduate, applied disciplinary curricula - Hewlett, L (South African Journal of Higher Education, 2016)
Interdisciplinarity is widely claimed as a core feature of, and rationale for, the development of postgraduate programmes in applied disciplinary fields. While there is considerable debate about the nature of interdisciplinarity, less consideration is given to the concept of curriculum and what ‘being interdisciplinary’ implies for the selection and organisation of knowledge in a curriculum aspiring to some level of interdisciplinarity. Drawing on sociological analyses of curriculum this paper explores Bernstein’s concepts of integrated-type curricula and recontextualisation and uses these concepts to explore the complexities of attempting to use interdisciplinarity as an integrating logic in a Public Management curriculum. Findings from the analysis of documentary and interview data highlight how interdisciplinarity was difficult to develop and sustain as a curriculum integrating logic over time. Without a strong consensus about the integrating interdisciplinary idea and the knowledge that underpinned it, relationships between the relational idea and curriculum content became increasingly implicit, individually interpreted and disabling for a shared sense of purpose and progression across the degree. Development of programmes that call themselves interdisciplinary requires an understanding of curriculum as selection and organisation of knowledge from within disciplines and, in the case of applied disciplinary fields, from workplace practice.